Damage to DNA caused by UV-B radiation in the desert cyanobacterium Scytonema javanicum and the effects of exogenous chemicals on the process - Wang, Gaohong; Deng, Songqiang; Li, Cheng; Liu, Yongding; Chen, Lanzhou; Hu, Chaozhen (Chemosphere (Oxford), 2012)
► UV-B radiation induced DNA damage in cyanobacteria. ► Antioxidants NAC and ASC decreased DNA damage and ROS under UV-B. ► Herbicides (GPS and MCPA) increased DNA damage and ROS under UV-B. ► DNA damage induction and chemicals effects were mediated by ROS regulation. Radiation with UV-B increased the damage to DNA in Scytonema javanicum, a desert-dwelling soil microorganism, and the level of damage varied with the intensity of UV-B radiation and duration of exposure. Production of reactive oxygen species (ROS) also increased because of the radiation. Different exogenous chemicals (ascorbate acid, ASC; N-acetylcysteine, NAC; glyphosate, GPS; and 2-methyl-4-chlorophenoxyacetic acid, MCPA-Na) differed in their effect on the extent of DNA damage and ROS production: whereas NAC and ASC protected the DNA from damage and resulted in reduced ROS production, the herbicides (GPS and MCPA-Na) increased the extent of damage, lowered the rate of photosynthesis, and differed in their effect on ROS production. The chemicals probably have different mechanisms to exercise their effects: NAC and ASC probably function as antioxidant agents or as precursors of other antioxidant molecules that protect the DNA and photosynthetic apparatus directly from the ROS produced as a result of UV-B radiation, and GPS and MCPA-Na probably disrupt the normal metabolism in S. javanicum to induce the leaking of ROS into the photosynthetic electron transfer pathway following UV-B radiation, and thereby damage the DNA. Such mechanisms have serious implications for the use of environment-friendly herbicides, which, because they can destroy DNA, may prove harmful to soil microorganisms.